Thick braneworlds and the Gibbons-Kallosh-Linde no-go theorem in the Gauss-Bonnet framework - Dias, M.; Hoff da Silva, J. M. [UNESP]; Rocha, Roldao da (Epl Association, European Physical Society, 2015)
The sum rules related to thick braneworlds are constructed in order to encompass Gauss-Bonnet terms. The generation of thick branes is hence proposed in a periodic extra dimension scenario, which circumvents the Gibbons-Kallosh-Linde no-go theorem in this context. Copyright (C) EPLA, 2015